PENGEMBANGAN USAHA BUDIDAYA KEPITING DALAM KAWASAN HUTAN MANGROVE MELALUI SISTEM SILVOFISHERY YANG BERBASIS MASYARAKAT - Rustam, Rustam; Hamsiah, Hamsiah; Hartinah, Hartinah (Jurnal BALIRESO, 2020)
The purpose of this community partnership empowerment (PKM) activity is 1) to provide knowledge and skills to fishermen groups about enlarging crab crabs with silvofishery systems; 2) optimally and sustainably utilizing mangrove forest resources; and 3) increase added value and employment opportunities for coastal communities. The method of activity includes: 1) socialization and demonstration; 2) monitoring and evaluation includes the initial, mid and final stages of program implementation. The targets and outcomes of the community partnership empowerment (PKM) activities are 1) creating alternative livelihoods for the people in the coastal areas, especially around the mangrove forest area through an effort to enlarge crabs so that their income can increase; 2) carry out mangrove forest conservation through mangrove forests with cultivation technology using cages or silvofishery systems; 3) forming community business units that implement good production management and business management systems; and 4) maintain continuity of production and fulfill market needs for crab crabs. An understanding of mangroves and the cultivation of crabs with silvofishery systems in learning for the community as outlined in the training and practice activities is well understood to carry out these activities.